Consumer Protection under Shariah Law in Islamic Religious Tourism - Rahman, Wan Farahiyah Izni W Abd; Ahamat, Haniff (International Journal of Asian Social Science, 2020)
Consumer protection mentions about safeguards against wrongful conduct by service providers that adversely affect consumers. In Malaysia, the field that seems to be ignored is the protection of Muslim tourists in Islamic religious tourism industry. Despite the fact that the Islamic religious tourism service is important and Hajj and Umrah travel package is regularly used by consumer in Malaysia. The number of complaints in relation to this service continued to increase annually. In fact, the complaints against the Hajj and Umrah travel agents were the highest in the Tribunal list of filed services case. The aim of this article is to examine the rules and principles under the Shariah law that gives protection to consumers in the Islamic religious tourism. The legal study conducted was indeed qualitative in nature. Being so, this study collects relevant data which related to consumer protection under Shariah law in Islamic religious tourism. The discussion focuses on the Shariah laws and references are made to the thoughts of four scholars in Islam. The study suggests that there is a need to amend the consumer protection for Muslim tourists in Islamic religious tourism. Malaysia should adopt Shariah principles into consumer protection of Muslim tourists guideline and legislation so as to strengthen the protection of consumer in Islamic religious tourism industry.